Black Carbon and Inorganic Aerosols in Arctic Snowpack. Issue 23 (14th December 2019) - Mori, Tatsuhiro; Goto‐Azuma, Kumiko; Kondo, Yutaka; Ogawa‐Tsukagawa, Yoshimi; Miura, Kazuhiko; Hirabayashi, Motohiro; Oshima, Naga; Koike, Makoto; Kupiainen, Kaarle; Moteki, Nobuhiro; Ohata, Sho; Sinha, P.R.; et al.
Abstract: Black carbon (BC) deposited on snow lowers its albedo, potentially contributing to warming in the Arctic. Atmospheric distributions of BC and inorganic aerosols, which contribute directly and indirectly to radiative forcing, are also greatly influenced by depositions. To quantify these effects, accurate measurement of the spatial distributions of BC and ionic species representative of inorganic aerosols (ionic species hereafter) in snowpack in various regions of the Arctic is needed, but few such measurements are available. We measured mass concentrations of size‐resolved BC ( C MBC ) and ionic species in snowpack by using a single‐particle soot photometer and ion chromatography, respectively, over Finland, Alaska, Siberia, Greenland, and Spitsbergen during early spring in 2012–2016. Total BC mass deposited per unit area (DEPMBC ) during snow accumulation periods was derived from C MBC and snow water equivalent (SWE). Our analyses showed that the spatial distributions of anthropogenic BC emission flux, total precipitable water, and topography strongly influenced latitudinal variations of C MBC, BC size distributions, SWE, and DEPMBC . The average size distributions of BC in Arctic snowpack shifted to smaller sizes with decreasing C MBC due to an increase in the removal efficiency of larger BC particles during transport from major sources. Our measurements of C MBC were lower by a factor of 13 than previous measurements made with an Integrating Sphere/Integrating Sandwich spectrophotometer due mainly to interference from coexisting non‐BC particles such as mineral dust. The SP2 data presented here will be useful for constraining climate models that estimate the effects of BC on the Arctic climate. Plain Language Summary: Black carbon (BC) particles, commonly known as soot, are emitted from incomplete combustion of fossil fuels and biomass. They efficiently absorb solar radiation and thus heat the atmosphere. BC particles emitted at midlatitudes and in the Arctic are deposited onto snow in the Arctic, accelerating snowmelt in early spring by absorbing solar radiation. These processes contribute to warming in the Arctic. Calculations of this warming effect by using numerical models need to be validated by comparison with observed BC concentrations in snowpack. However, there are very few accurate records of concentrations of BC in snow because of technical difficulties in making these measurements. We developed a new laser‐induced incandescence technique to measure BC concentrations in snowpack and applied it for the first time in six Arctic regions (Finland, Alaska, North and South Siberia, Greenland, and Spitsbergen). The BC concentrations we measured were highest in Finland and South Siberia, which are closer to large anthropogenic BC sources than the other regions, where our measured BC concentrations were much lower. On average, our BC concentrations were much lower than those previously measured by different techniques. Therefore, previous comparisons of modeled and observed BC concentrations need to be re‐evaluated using the present data. Key Points: First ever measurements with a high‐accuracy single‐particle soot photometer of black carbon (BC) concentrations in Arctic snowpack Topography and BC emission flux strongly influenced latitudinal variations of mass concentrations and size distributions of BC Measured BC mass concentrations 2–25 times lower than previously reported show the importance of revalidating climate models